Substitute 5 into both the equations...
-2 (5)+7=-3
5^2+9=34
-3+34=31
hope this helpsss
36:90 in simplest form would be
2:5-Love, live, and watch anime.
You would subitute -2 for x in the equation
f(-2)=x^2-6
PEMDAS so exonents
-2^2-6
negative times a negative= positive
4-6
f(-2)=-2
f(x) means that you subsitute x for x in the equation exg
f(1)=x+2 means f(1)=1+2
f(4)=x+2 means f(4)=4+2
-6+2
--------- =
10-10
-4
---- =
0
m=0
*(the "-----" are supposed to be fractions, sorry if that looks confusing)*
y+2=0(x-10)
y+2=0
-2 -2
y=-2
Your answer would be "y=-2."
Answer:
![l=\dfrac{2(S-b)}{P}](https://tex.z-dn.net/?f=l%3D%5Cdfrac%7B2%28S-b%29%7D%7BP%7D)
Step-by-step explanation:
The surface area formula for pyramids is given by :
...(1)
We need to arrange the formula for l.
Take b to LHS,
![S-b=\dfrac{1}{2}Pl\\\\2(S-b)=Pl\ [\text{cross-multiplying}]\\\\l=\dfrac{2(S-b)}{P}](https://tex.z-dn.net/?f=S-b%3D%5Cdfrac%7B1%7D%7B2%7DPl%5C%5C%5C%5C2%28S-b%29%3DPl%5C%20%5B%5Ctext%7Bcross-multiplying%7D%5D%5C%5C%5C%5Cl%3D%5Cdfrac%7B2%28S-b%29%7D%7BP%7D)
So, the expression is
for the slant height.